Visual Campaign Strategies and Positive Narratives to Improve Student Character in Elementary Schools: Community Service Study in Mataram - faqih, m; Iqbal, Muhammad; Jaswandi, Jaswandi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The problem of students who tend to have negative narratives about themselves is a challenge in character development. This community service activity aims to create a visual campaign strategy and positive narrative to strengthen the character of students in elementary schools in Mataram. The methods used include workshops on creating positive narratives and visualizations, teacher training, and collaboration with parents. The results show that students are starting to be able to describe themselves as honest, disciplined and caring individuals. Teachers and parents also make significant contributions in supporting program implementation. The impact can be seen in changes in students' mindsets that are more positive and increased collaboration between the school and families. This activity provides a strategic model to be applied in various other educational institutions.